1981
DOI: 10.1139/z81-255
|View full text |Cite
|
Sign up to set email alerts
|

The population structure of Simulium vittatum (Zett.): the IIIL-1 and IS-7 sibling species

Abstract: This paper describes two sibling species in Simulium vittatum (Zett.) on the basis of their salivary gland chromosomes. The IIIL-1 sibling is characterized by a Y chromosome carrying the IIIL-1 inversion; the IS-7 sibling is characterized by the IS-7 X chromosome. The basic banding sequences are identical in the two sibling species. The siblings differ however in the relative frequencies of standard and inverted sequences for a number of autosomal polymorphisms that they share. Standard sequences are predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 9 publications
4
34
2
Order By: Relevance
“…These populations showed similar banding patterns on their polytene chromosomes and could be differentiated only on the basis of inversion polymorphisms (Kiknadze et al 1996). A tendency to monomorphism is often found in isolated populations (Carson 1959, Heed & Russell 1971, Rothfels & Featherston 1981 but S. pertinax populations are not isolated. The use of insecticides during more than two decades may have contributed to the homogeneity of these populations by reducing their chromosomal variability.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These populations showed similar banding patterns on their polytene chromosomes and could be differentiated only on the basis of inversion polymorphisms (Kiknadze et al 1996). A tendency to monomorphism is often found in isolated populations (Carson 1959, Heed & Russell 1971, Rothfels & Featherston 1981 but S. pertinax populations are not isolated. The use of insecticides during more than two decades may have contributed to the homogeneity of these populations by reducing their chromosomal variability.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, analysis of 299 larvae demonstrated chromosomal homosequentiality among six populations from different sites, indicating that S. pertinax is a monotypic species, with little variation in its polytene chromosomes. Chromosomal homosequentiality may also occur among morphospecies (Bedo 1979a, Rothfels & Featherston 1981, Henderson 1986), although this is an exception in Simuliidae (White 1977.…”
Section: Discussionmentioning
confidence: 99%
“…Some species are medically and economically important, such as the vectors of filarial worms that cause onchocerciasis. Simulium vittatum, which is found throughout North America as well as in Greenland, Iceland, and the Faroe Islands, is a pest of domesticated and wild large mammals (Rothfels and Featherston 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Simulium vittatum has been well characterized cytogenetically (Rothfels and Dunbar 1953;Pasternak 1964;Rothfels and Featherston 1981). Pasternak (1964) provided polytene chromosome maps of S. vittatum and an analysis of inversion polymorphisms in natural populations, noting significant mutual exclusion of the IIIL-1 and IS-7 inversions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation